BUDAYA ORGANISASI, KEPEMIMPINAN, DAN KOMUNIKASI TERHADAP PRESTASI KERJA PEGAWAI DINAS PEKERJAAN UMUM KABUPATEN TAKALAR - Guntur Suryo Putro (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The purpose of this study is whether the organizational culture, leadership and communication affect the performance peagawai. Penelituian type is quantitative research. The results of this study are based on testing F obtained that independent variables such as organizational culture, leadership and communication together or simultaneously significant effect on the dependent variable / performance is evidenced by the large value of F count> F table (8629> 2740). Based on test results obtained by the value of the coefficient of determination of 24.9%. This means that 24.9% of employees work performance variables environment of the Public Works Department can be explained by the presence of variable organizational culture, leadership and communication although the effect was not as great.